Ranljivost na podnebne spremembe in participacija - Švigelj, Ivo (Družboslovne razprave, 2016)
The following study tries to establish whether it is possible to ascertain participation as an important factor of vulnerability to climate change. The thesis is therefore: the quality of participation influences vulnerability to climate change. In order to examine the thesis, vulnerability to climate change is defined, and the quality of participation is operationalised with the five most important dimensions. This model is then applied to a case study of a decision-making process on flood protection measures for south-west Ljubljana. Semi -structured in-depth interviews and an analysis of written communication sources are used. Important deficiencies regarding all five of the most important dimensions of participation are discovered and, therefore, it can be concluded that in the analysed case a low quality of participation enabled the vulnerability to remain high.
Keywords: Climatic changes; Podnebne spremembe; Threatening; Ogroženost; Participacija; Participation; poplavna varnost; Ljubljana